1990
DOI: 10.1128/jb.172.8.4529-4535.1990
|View full text |Cite
|
Sign up to set email alerts
|

The leucine regulon of Escherichia coli K-12: a mutation in rblA alters expression of L-leucine-dependent metabolic operons

Abstract: We have isolated and characterized a highly pleiotropic Escherichia coli mutant affected in the activity of a number of enzymes involved in different metabolic pathways, all of which are regulated by leucine. Selected for its ability to grow with L-serine as sole carbon source, the rbl-1::TnlO mutant had high levels of L-serine deaminase activity (due to increased transcription of the structural gene) and of another amino acid-degrading enzyme, L-threonine dehydrogenase, and decreased transcription of the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…,B-Galactosidase assays on these strains showed that the serA promoter is present on this DNA fragment ( Table 5). As shown previously (43), serA was constitutively repressed in an lrp::TnJO strain. Interestingly, the serA promoter was constitutively induced in the livR strain (Table 5).…”
Section: Consensus T T T a T T C T N A A T A Within The Regions Recogmentioning
confidence: 72%
See 3 more Smart Citations
“…,B-Galactosidase assays on these strains showed that the serA promoter is present on this DNA fragment ( Table 5). As shown previously (43), serA was constitutively repressed in an lrp::TnJO strain. Interestingly, the serA promoter was constitutively induced in the livR strain (Table 5).…”
Section: Consensus T T T a T T C T N A A T A Within The Regions Recogmentioning
confidence: 72%
“…The sequence of the serA promoter has not been reported. Tuan et al (43) have shown that serA is regulated by Lrp and leucine. A segment of DNA containing serA and its natural promoter, along with a preliminary sequence of the promoter region, was obtained from G. Grant.…”
Section: Consensus T T T a T T C T N A A T A Within The Regions Recogmentioning
confidence: 99%
See 2 more Smart Citations
“…In our earlier work, we showed that expression from the metK promoter is repressed by the regulatory protein Lrp and induced by leucine, which combines with Lrp and removes it from the promoter (Tuan et al, 1990). Strain MEW402 carries the metK84 mutation, a single base pair change next to the metK promoter, and as a result greatly underproduces SAM synthase unless provided with leucine to increase metK expression (Wei & Newman, 2002).…”
Section: (R)-sam and (S)-sammentioning
confidence: 99%